Flaxseed Ingestion Alters Ratio of Enterolactone Enantiomers in Human Serum - Niina M. Saarinen; Annika I. Smeds; José L. Peñalvo; Tarja Nurmi; Herman Adlercreutz; Sari Mäkelä (Journal of Nutrition and Metabolism)
Enterolactone (EL) is an enterolignan found in human subjects. In this pilot study, the enantiomeric ratios of serum EL were determined in serum from healthy adults during consumption of habitual diet, and after an 8-day supplementation with flaxseed (25 g/day). (−)EL dominated in all serum samples collected during habitual diet consumption. However, the ratio of (−)EL and (+)EL enantiomers differed markedly between individuals. Flaxseed ingestion increased significantly the proportion of (+)EL in all subjects. Moreover, a small but significant increase in serum (−)EL concentration was measured. After flaxseed ingestion, (−)EL concentrations correlated with those of (+)EL suggesting that the stereochemistry of the parent plant lignan in flaxseed is not a major determinant of EL formation in human subjects. Comparison of EL concentrations obtained with the validated chromatographic methods (HPLC-MS/MS, HPLC-CEAD, and GC-MS) and the time-resolved fluoroimmunoassay (TR-FIA) revealed that the immunoassay method underestimates human serum EL concentrations after the flaxseed ingestion.